2022
DOI: 10.1002/mop.33219
|View full text |Cite
|
Sign up to set email alerts
|

A compact self‐packaged triple‐mode bandpass filter using dual capacitively‐loaded substrate‐integrated waveguide resonator

Abstract: A compact triple‐mode (TM) bandpass filter (BPF) is designed based on the proposed dual capacitively‐loaded (DCL) substrate‐integrated waveguide (SIW) resonator. Two identical T‐shaped grounded striplines are inserted into a square SIW cavity to generate a capacitively loading effect without damaging cavity surface integrity, which contributes to maintaining EM‐shielding capability. By adjusting the size and position of the DCL structure, the first three resonant modes, including TE101, TE201, and TE301 are ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
(20 reference statements)
1
5
0
Order By: Relevance
“…The DCL structure generates a capacitive perturbation effect and causes resonant frequencies to shift lower. It is similar to the one in Jing et al 12 However, the difference is that the modes utilized in this study are TE 101 , TE 102 , and TE 201 , while those in Jing et al 12 are TE 101 , TE 102 , and TE 103 .…”
Section: Basic DCL Tm Resonator Analysissupporting
confidence: 75%
See 2 more Smart Citations
“…The DCL structure generates a capacitive perturbation effect and causes resonant frequencies to shift lower. It is similar to the one in Jing et al 12 However, the difference is that the modes utilized in this study are TE 101 , TE 102 , and TE 201 , while those in Jing et al 12 are TE 101 , TE 102 , and TE 103 .…”
Section: Basic DCL Tm Resonator Analysissupporting
confidence: 75%
“…In recent years, substrate integrated waveguide (SIW)‐based multimode resonators have aroused much interest in filter design due to their excellent filtering performance and inherent small size. A multitude of multimode SIW filters are designed based on higher order modes only 1–3 or dominant mode 4–12 . Despite the fact that the higher order modes‐based filters have easy control of resonant modes and good out‐of‐band rejection both below and above the passband, using them will expand the overall size of the filter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolation achieved is better than that of Zhou and Wu 10 and Zhan et al 22 Meanwhile, the number of TZ's achieved is one less than what is reported in Zhao et al 14 and Zhou et al 17 and one more than the others. This work's insertion loss is better than, 10,14,17,19 and isolation higher than refs 7,17,19 …”
Section: Fabrication and Measurementmentioning
confidence: 66%
“…2 Furthermore, because of its tolerance to high power, lower insertion loss, and compatibility, substrateintegrated waveguide (SIW) technology has been used in several recent designs of microwave and millimeter-wave devices. [3][4][5][6][7][8][9] To meet the demands and technological standards, much attention has been focused on designing many filtering channels using the SIW. To investigate the benefits of multichannel BPF, a five-channel filtering crossover was reported, 10 which exploited the tendencies of specified "frequency flexibility" for two separate frequency bands and "quadruple mode in a single cavity."…”
Section: Introductionmentioning
confidence: 99%